Population biology of the porcelain crab Pachycheles laevidactylus Ortmann, 1892 (Anomura: Porcellanidae) in the Southwestern Atlantic - Mosna, E. E.D. [UNESP]; João, M. C.A. [UNESP]; Hernáez, P.; Ferreira, L. A.A.; Noori, A.; Pinheiro, M. A.A. [UNESP] (Taylor & Francis, 2023)
A population of the porcelain crab Pachycheles laevidactylus was evaluated based on sex ratio, sexual dimorphism, reproductive intensity, relative growth and sexual maturity. The porcelain crabs were identified, sexed and measured as follows: carapace (CL, length; CW, width), chelar propodus (PL, length; PH, height) and abdomen (AL, length; AW2 and AW5, the width of the 2nd and 5th abdominal somite, respectively). For the 1,109 specimens analyzed, the sex ratio was 1:1, but contrasted in some seasons. Females were significantly larger than males, and ovigerous females were recorded in all seasons, with greater intensity in autumn and winter. In males, the biometric ratios of the major chelar propodus (PHxCL and PLxCL) showed positive allometry regarding body size, with a reduction in the allometry rate after puberty. The same occurred with females for the biometric ratios of the abdomen (AW2xCL and AW5xCL). Males attain morphological sexual maturity at 3.48 mm CL, earlier than females, which occurred at 5.00 mm CL. In this study, P. laevidactylus matured with a larger size than reported for others analyzed in the temperate zone. It is the first study addressing aspects of the population biology of P. laevidactylus in a region with a subtropical climate.
Keywords: Allometry; growth; morphology; reproduction; sexual maturity